2016
DOI: 10.4314/gjass.v15i1.1
|View full text |Cite
|
Sign up to set email alerts
|

Profitability of groundnut-based cropping systems among farmers in Hong local government area of Adamawa state, Nigeria

Abstract: Groundnut is an important cash crop and a good source of vegetable oil to resource-poor farmers. The study examined the Profitability of Groundnut-based Cropping Systems among farmers in Hong Local Government Area of Adamawa State, Nigeria. Specifically, the socioeconomic characteristics of the farmers were described, their cropping systems identified, and the profitability of groundnut-based cropping systems determined. Multi-stage random sampling was used in selecting one hundred and twenty respondents used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
2
0
0
Order By: Relevance
“…Thus, the marginal and elasticity implications of a unit increase in the use of herbicides by 1 litre would increase output level by 115.95kg and 0.091% respectively. This agrees with the findings of Bathon et al (2016) and Thulasiram et al (2018) who in their various research reported a direct relation between biocides and groundnut output level. The negative significance of the fertilizer coefficient revealed an over-dosage in the application of the agro-chemical.…”
Section: Production Estimates and Inputs Allocation Efficiencysupporting
confidence: 93%
See 1 more Smart Citation
“…Thus, the marginal and elasticity implications of a unit increase in the use of herbicides by 1 litre would increase output level by 115.95kg and 0.091% respectively. This agrees with the findings of Bathon et al (2016) and Thulasiram et al (2018) who in their various research reported a direct relation between biocides and groundnut output level. The negative significance of the fertilizer coefficient revealed an over-dosage in the application of the agro-chemical.…”
Section: Production Estimates and Inputs Allocation Efficiencysupporting
confidence: 93%
“…Therefore, the marginal and elasticity implications of a unit increase in the farm size by 1 hectare would increase output by 222.78kg and 0.328% respectively. This conforms with the findings of Bathon et al (2016) and Audu et al (2017). The positive significant of the herbicides coefficient signified the appropriate dosage application of the agrochemical, thus exerting a positive influence on the output level of groundnut in the studied area.…”
Section: Production Estimates and Inputs Allocation Efficiencysupporting
confidence: 90%